Indiana's Reward-for-Effort School Funding Formula: Issues and Options - Neil D. Theobald; Barry Bull; Nick Vesper (Educational Considerations, 1997)
Indiana is in the fourth year of a scheduled six-year phase in of its guaranteed yield Reward-for-Effort School Funding Formula.